КЫРГЫЗ РЕСПУБЛИКАСЫНЫН ЕВРАЗИЯ ЭКОНОМИКАЛЫК БИРИМДИГИНИН АЛКАГЫНДА МОНОПОЛИЯГА КАРШЫ ЖӨНГӨ САЛУУ: ИНТЕГРАЦИЯНЫН 10 ЖЫЛЫ, НАТЫЙЖАЛАРЫ ЖАНА КЕЛЕЧЕГИ (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The report examines the outcomes of the Kyrgyz Republic’s ten-year participation in the Eurasian Economic Union (EAEU) in the field of competition and antimonopoly regulation. Special attention is given to the transformation of national antimonopoly policy, the harmonization of legislation, institutional cooperation with the Eurasian Economic Commission (EEC), as well as the impact on the business environment, investment climate, and digital economy. The report highlights sectors that have received a development boost, identifies existing barriers, and outlines key directions for improving the system.
Keywords: EAEU, antimonopoly regulation, competition, Kyrgyzstan, cross-border markets, EEC, investment climate, digital economy